(untitled) (Al-Aasar, 2026)
This research paper analyzes the theological and reformative methodologies embedded within the Pashto exegetical notes (Tafseeri Fawaid) of the prominent 20th-century scholar, Sheikh-ul-Quran Maulana Qazi Abdul Hadi Rustami, with a specific case study of Surah Yunus. Hailing from the illustrative Qazian family of Rustam, Mardan, and academically nurtured by legendary subcontinental stalwarts at Deoband and Saharanpur, Maulana Rustami’s intellectual framework uniquely synthesized spiritual purification with rigorous scholarship. This study demonstrates that his theological approach consciously eschews speculative Greek philosophical complexities, aligning instead with the balanced, traditional paradigm of the Salaf (pious predecessors) regarding divine attributes and predestination. Concurrently, his dynamic reformative stance vigorously combats contemporary societal innovations, moral decay, and psychological shortcomings. Methodologically, he brilliantly utilizes contextual indigenous Pashto proverbs to demystify intricate monotheistic tenets for the masses, while launching a robust critique against modern ethnic and territorial nationalism, characterizing it as a form of Pharaonic neo-Jahiliyyah. Ultimately, this paper highlights how Maulana Rustami presents the Quran not merely as a theoretical text, but as a living, transformative manual for contemporary intellectual and socio-political rectification.